Influence of opening on the behaviour of bamboo reinforced concrete wall panels under two way in-plane action - Ganesan, N.; Indira, P.V.; Himasree, P.R. (Journal of Structural Engineering, 2024)
The paper presents the influence of opening on the performance of bamboo reinforced concrete wall panels under two way in-plane action. Six prototype bamboo reinforced concrete wall panel specimens were tested for failure under uniformly distributed load that was applied at an eccentricity of one-sixth the thickness of the wall panel. Of the six specimens considered in this study, three were solid wall panels, and the rest three possess opening at its centre. The specimens considered were having a constant slenderness ratio of 25 with varying values of aspect ratios of 1.67, 1.82 and 2 and thinness ratios of 12.50, 13.75 and 15. Area of the opening provided was exactly 25% of the area of the specimen. The study indicates that the ultimate load of wall panels decreases with an increase in aspect ratio regardless of the presence of the opening. Also, ultimate load increases with the increase in thinness ratio.